Share
Explore BrainMass

Linear Fractional Transformations and Implicit Form

Let T(z) = (az+b)/(cz+d), where ad-bc≠0, be any linear fractional transformation other than T(z) = z. Show that T^-1 = T only if d = -a.

Attachments

Solution Preview

T=(az+b)/(cz+d)

First we have to find the inverse. To do so we must solve the above equation in z.

(cz+d)T=(az+b) ---> czT+dT=az+b ---> czT-az=b-dT ---> z=(b-dT)/(cT-a)

At this point if we let z be T^(-1) and T be z in the above ...

Solution Summary

Linear Fractional Transformations and Implicit Form are investigated.

$2.19